Mex3a-dependent post-transcriptional silencing ensures olfactory receptor diversity and axon guidance specificity - Rachel Duffié; Hani Shayya; Martín Escamilla del Arenal; Miao Wang; Jerome Kahiapo; Aileen Ugurbil; Abdurrahman Keskin; Fiona Clowney; Elizaveta V. Bashkirova; Ariel D. Pourmorady; Ira Schieren; Humberto Ibarra Avila; et al. (Cell Reports)
Summary: Olfactory sensory neurons (OSNs) use olfactory receptor (OR)-specific patterns of endoplasmic reticulum (ER) stress to transform OR sequence identity into axon guidance precision. However, during neuronal differentiation, OSNs transiently co-express random combinations of OR genes, which could generate unpredictable ER stress signatures that could lead to axon miswiring. Here, we show that post-transcriptional OR silencing by the transiently expressed and cytoplasmic RING and KH domain protein Mex3a, decouples OR transcription from OR protein-induced ER stress, until the onset of singular OR transcription. Consequently, conditional Mex3a deletion results in premature ER stress during the polygenic stage of OR transcription, which biases OR choice toward the OR alleles that are transcribed first and perturbs the specificity of OR-regulated axon targeting, disrupting the glomerular map of odor representation in the olfactory bulb. Our experiments reveal the critical role of post-transcriptional gene regulation in a fundamental cellular pathway that influences the assembly of neuronal circuits.